Research advances in mesenchymal stem cells and related therapies for rotator cuff tendon-to-bone healing - Song, Laimeng; Li, Na; Chen, Jiwu (Frontiers in Bioengineering and Biotechnology, 2025)
Rotator cuff tears (RCTs) are a prevalent cause of shoulder dysfunction, with postoperative retearing remaining a significant challenge due to poor tendon-to-bone healing. Mesenchymal stem cells (MSCs), owing to their multipotency, immunomodulatory properties, and diverse tissue sources, have emerged as a promising therapeutic strategy. Current approaches include direct MSC implantation, MSC-laden scaffolds for structural support, and utilization of MSC-derived conditioned medium (CM) or exosomes to enhance regeneration. Clinical studies demonstrate reduced retear rates with MSC-based therapies, yet animal models show inconsistent outcomes, influenced by cell source, delivery methods, and dosage. MSC modifications (e.g., gene editing) and scaffold-based strategies further improve biomechanical strength and fibrocartilage regeneration. Emerging focus on MSC secretome, particularly exosomes, highlights their potential in modulating inflammation and tissue repair. While preclinical results are encouraging, clinical translation requires standardization of protocols, optimization of delivery systems, and long-term safety evaluations.